1991
DOI: 10.1038/bjc.1991.412
|View full text |Cite
|
Sign up to set email alerts
|

The effect of circulating antigen and radiolabel stability on the biodistribution of an indium labelled antibody

Abstract: Summary This study has investigated two of the main problems with radiolabelled antibody imaging, the formation of circulating immune complexes (I.C.) and the non specific binding of radiolabel to the antibody molecule.Patients undergoing immunoscintigraphy with "'In labelled monoclonal antibody ICR2 were divided into three groups who received either the radiolabelled antibody alone (control, n = 12), the radiolabelled antibody which was incubated with the chelating agent diethylene triamine pentacetic acid (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…However, Koji et al [7] and Ishii et al [8] reported that anti-AFP antibodies were deliv ered to hepatoma cells in spite of the presence of enough serum AFP to neutralize them. Similar results were reported with systems using anti-CEA MoAb [4] and other MoAbs [3,9], indicating that circulating antigen did not always interfere with tumor targeting. These results suggest that even circulating an tigens such as AFP or CEA can be suitable tar get candidates for tumor targeting when the selection of MoAbs against them is well op timized as targeting carriers.…”
Section: Introductionsupporting
confidence: 75%
“…However, Koji et al [7] and Ishii et al [8] reported that anti-AFP antibodies were deliv ered to hepatoma cells in spite of the presence of enough serum AFP to neutralize them. Similar results were reported with systems using anti-CEA MoAb [4] and other MoAbs [3,9], indicating that circulating antigen did not always interfere with tumor targeting. These results suggest that even circulating an tigens such as AFP or CEA can be suitable tar get candidates for tumor targeting when the selection of MoAbs against them is well op timized as targeting carriers.…”
Section: Introductionsupporting
confidence: 75%
“…The high level of urinary excretion of "'In at 2 h p.i., which seems higher than that of l4C (difference not sig nificant), seems to support the suggestion by Davidson and co-workers that a part of the "'In is not tightly bound to the IgG [15]. In vitro, however, '" In-DTPAIgG-('4C) appears to be rather stable (cf.…”
Section: Discussionsupporting
confidence: 64%
“…Lack of immunodetection and complications associated With MAb cross-reactive with circulating cells had been reported (Diliman et al. 1984 labelled MAb which formed a circulating immune complex have been reported (Hnatowich et al, 1987;Davidson et al, 1991). In the present study, increased liver uptake of radiolabelled MAb was noted as in the previous studies, although the pharmacokinetics were different and imaging was not successful.…”
Section: Materids and Methodssupporting
confidence: 56%